An Expedient Synthesis of Pyrrolo[3, 2, 1‐ij]quinoline‐1, 2‐diones via Intramolecular Friedel–Crafts Cyclization Protocol. (28th September 2015) - Moon, Hye Ran; Kim, Su Yeon; Lim, Jin Woo; Kim, Jae Nyoung
Abstract :